Educating Mind, Body and Spirit: The legacy of Quintin Hogg and The Polytechnic, 1864-1992 - Glew, Helen; Gorst, Anthony; Heller, Michael; Matthews, Neil (University of Westminster Press, 2013)
The story of the Polytechnic and of the legacy of Quintin Hogg is the third publication exploring the University of Westminster's long and diverse history. A fitting tribute to the life and legacy of Hogg, his holistic approach to education and the institute he created. This book is richly illustrated with images from the University's Archive.